Actual and Illusory Perception in Parkinson's Disease and Dystonia: A Narrative Review - Avanzino, Laura; Fiorio, Mirta; Conte, Antonella (Frontiers in Neurology, 2018)
Sensory information is continuously processed so as to allow behaviour to be adjusted according to environmental changes. Before sensory information reaches the cortex, a number of subcortical neural structures select the relevant information to send to be consciously processed. In recent decades, several studies have shown that the pathophysiological mechanisms underlying movement disorders such as Parkinson’s disease (PD) and dystonia involve sensory processing abnormalities related to proprioceptive and tactile information. These abnormalities emerge from psychophysical testing, mainly temporal discrimination, as well as from experimental paradigms based on bodily illusions. Although the link between proprioception and movement may be unequivocal, how temporal tactile information abnormalities and bodily illusions relate to motor disturbances in PD and dystonia is still a matter of debate. This review considers the role of altered sensory processing in the pathophysiology of movement disorders, focusing on how sensory alteration patterns differ between PD and dystonia. We also discuss the evidence available and the potential for developing new therapeutic strategies based on the manipulation of multi-sensory information and bodily illusions in patients with these movement disorders.